The hypotensive effect of the aqueous calyx extract of Hibiscus sabdariffa may occur through the attenuation of Autonomic nervous system activity (Nigerian Journal of Physiological Sciences, 2021)
This study tested the hypothesis that the hypotensive effect of the aqueous calyx extract of Hibiscus sabdariffa (HS) occurs through autonomic mechanisms that may be associated with a reduction in the double product (DP) of the heart. Experiments were performed in accordance with the Principles of the Declaration of Helsinki. Following ethical approval and informed consent, the Harvard step test (HST) was performed in healthy subjects (n=14) to activate the autonomic nervous system before and after the oral administration of 15mg/kg HS. The blood pressure (BP) and heart rate (HR) responses were measured and DPs and the mean arterial pressure (MAP) were calculated. Results were expressed as mean ±SEM. Paired t-test and one way ANOVA with a posthoc Bonferoni test were used for statistical analyses. P